2020
DOI: 10.1093/nar/gkaa424
|View full text |Cite
|
Sign up to set email alerts
|

The translational activator Sov1 coordinates mitochondrial gene expression with mitoribosome biogenesis

Abstract: Abstract Mitoribosome biogenesis is an expensive metabolic process that is essential to maintain cellular respiratory capacity and requires the stoichiometric accumulation of rRNAs and proteins encoded in two distinct genomes. In yeast, the ribosomal protein Var1, alias uS3m, is mitochondrion-encoded. uS3m is a protein universally present in all ribosomes, where it forms part of the small subunit (SSU) mRNA entry channel and plays a pivotal role in ribosome loadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
0
14
0
1
Order By: Relevance
“…For the latter, such as in some members of the Capnodiales, Wai et al (2019) identified a nuclear-encoded ortholog of the mitochondrial-encoded version of rps3 . Among the metazoans and the fungi, the nuclear and mitochondrial versions of rps3 have been shown to be required for initiating protein translation and appear to have “moonlighting activities” by being involved in DNA repair, cell signaling, apoptosis, and potentially in gene regulation ( Neu et al, 1998 ; Kim et al, 2013 ; Wang et al, 2019 ; Seshadri et al, 2020 ). Maintaining the rps3 gene within the rnl group I intron might be a fortuitous association that provides the rps3 gene a locus embedded within an essential gene ( rnl ) presumable transcribed at a high rate, and this may “protect” the intron from being eroded by drift.…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, such as in some members of the Capnodiales, Wai et al (2019) identified a nuclear-encoded ortholog of the mitochondrial-encoded version of rps3 . Among the metazoans and the fungi, the nuclear and mitochondrial versions of rps3 have been shown to be required for initiating protein translation and appear to have “moonlighting activities” by being involved in DNA repair, cell signaling, apoptosis, and potentially in gene regulation ( Neu et al, 1998 ; Kim et al, 2013 ; Wang et al, 2019 ; Seshadri et al, 2020 ). Maintaining the rps3 gene within the rnl group I intron might be a fortuitous association that provides the rps3 gene a locus embedded within an essential gene ( rnl ) presumable transcribed at a high rate, and this may “protect” the intron from being eroded by drift.…”
Section: Discussionmentioning
confidence: 99%
“…These analyses revealed a heterogeneous group of proteins, most of which are directly involved in mitochondrial translation (Figure 4B). Along with nearby SSU proteins, we identified multiple translational activators, including Pet111 (Green-Willms et al, 2001), Pet54 (Naithani et al, 2003), Sov1 (Seshadri et al, 2020), Cbs2 (Muroff and Tzagoloff, 1990;Rö del, 1986), and Aep1 (Payne et al, 1991(Payne et al, , 1993, which are specific for translation of COX2, COX3, VAR1, COB, and ATP9 mRNAs, respectively. Moreover, other proteins involved in translation were found, namely, Aim23, the mitochondrial IF3 (Kuzmenko et al, 2016), and Msc6, a PPR protein suggested to play a role in translation initiation (Franco et al, 2019).…”
Section: Ll Open Accessmentioning
confidence: 99%
“…Var1 is a mtDNA-encoded component of the mtSSU, and thus a decrease in its synthesis in turn potentially may compromise mitoribosomal function. Allotopic expression of a universal Var1 (Var1 u ) protein (i.e., as a functional chimera with a mitochondrial targeting signal) ( Seshadri et al. , 2020 ) did not restore the translational capacity of glucose-grown mrp7 (1-187) and mrp7 (1-146) cells, indicating that the mtVar1 levels were not the limiting factor for mitotranslation in these mutants under fermentation conditions (Supplemental Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…A mitochondrially targeted universal Var1 derivative (Var1 u ) was expressed in the indicated strains using the pRS316- VAR1 u plasmid ( Sanchirico et al. , 1995 ; Seshadri et al. , 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation